Pengelolaan Pembelajaran Tematik Kurikulum 2013 di SDN 1 Tirem Kecamatan Brati Kabupaten Grobogan - MUFRIDAH, MUFRIDAH, Prof. Dr. Bambang Sumardjoko, M.Pd, Dr. Sumardi, M.Si (2016)
The purpose of this study is to describe learning media on the implementation of Curriculum 2013 subthemes of thematic learning experiences of my childhood, to describe the learning material on the implementation of Curriculum 2013 subthemes of thematic learning experiences of my childhood, to describe the learning interaction on the implementation of Curriculum 2013 subthemes of thematic learning experiences of my childhood. This research type is qualitative and ethnographic design uses. Takes place at SDN 1 Tirem Brati Subdistrict Grobogan. Methods of data collection using in-depth interviews, observation, and documentation. Analysis of data starting from data reduction, data display, and conclusion drawing / verification. Test the validity of the data using a triangulation of sources and techniques. The results of this study are (1) Teachers using instructional media that has been provided by the government and also create their own learning media appropriate to the learning objectives to be achieved. Existing learning media provided by the government such as a book teacher and student books, media that they manage such media images projected various musical instruments teacher in visual media with the help of the LCD. (2) The subject matter in the form of knowledge packed in teaching material that includes knowledge of facts about the experience myself as a child, the concept of identifying symbols Pancasila, the principle of covering the place value of a number, the procedure includes counting the number to 40, the type of material that is affective covering thank the Lord, the material in the form of psychomotor aspects include games close your eyes and learn to swim (3) communication patterns in the study carried out in both directions between teachers and learners directly. The role of teachers in teacher learning as a primary learning resource for elementary school children also have a role as a support teacher or facilitator in the implementation of learning. Keywords: instructional media, teaching materials, interaction thematic learning, curriculum 2013